Longitudinal maturation of auditory cortical function during adolescence - Fitzroy, Ahren B.; Krizman, Jennifer; Tierney, Adam; Agouridou, Manto; Kraus, Nina (Frontiers in Human Neuroscience, 2015)
Cross-sectional studies have demonstrated that the cortical auditory evoked potential (CAEP) changes substantially in amplitude and latency from childhood to adulthood, suggesting that these aspects of the CAEP continue to mature through adolescence. However, no study to date has longitudinally followed maturation of these CAEP measures through this developmental period. Additionally, no study has examined the trial-to-trial variability of the CAEP during adolescence. To inform these issues, we longitudinally tracked changes in the latency, amplitude, and variability of the P1, N1, P2, and N2 components of the CAEP in 68 adolescents from age 14 years to age 17 years. Latency decreased for N1 and N2, and did not change for P1 or P2. Amplitude decreased for P1 and N2, increased for N1, and did not change for P2. Variability decreased with age for all CAEP components. These findings provide longitudinal support for the view that the human auditory system continues to mature through adolescence. Continued auditory system maturation through adolescence suggests that CAEP neural generators remain plastic during this age range and potentially amenable to experience-based enhancement or deprivation.